The interplay of data, consumer and Private International law rules in the area of collective access to justice in the European Union - Agulló Agulló , Diego (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The objectives of this essay are to address the relationship between public and private enforcement of the rights contained in the General Data Protection Regulation (GDPR) in terms of data protection representative actions; to make a general overview of Directive 2020/1828 and to analyze to what extent a systematic interpretation of the various rules of different legal disciplines that may be involved in representative actions is possible and desirable. Furthermore, this paper addresses the question whether the introduction in the GDPR of new heads of international jurisdiction is appropriate and how these relate to the classical heads of jurisdiction of Regulation 1215/2012 that may be applicable in the area of representative actions.
Keywords: representative actions; data protection; consumers